Analysis of spatial and temporal dynamics of xylem refilling in Acer rubrum L. using magnetic resonance imaging - Zwieniecki, Maciej A.; Melcher, Peter J.; Ahrens, Eric (Frontiers in Plant Science, 2013)
We report results of an analysis of embolism formation and subsequent refilling observed in stems of Acer rubrum L. using magnetic resonance imaging (MRI). MRI is one of the very few techniques that can provide direct non-destructive observations of the water content within opaque biological materials at a micrometer resolution. Thus, it has been used to determine temporal dynamics and water distributions within xylem tissue. In this study, we found good agreement between MRI measures of pixel brightness to assess xylem liquid water content and the percent loss in hydraulic conductivity (PLC) in response to water stress (P50 values of 2.51 and 2.70 for MRI and PLC, respectively). These data provide strong support that pixel brightness is well correlated to PLC and can be used as a proxy of PLC even when single vessels cannot be resolved on the image. Pressure induced embolism in moderately stressed plants resulted in initial drop of pixel brightness. This drop was followed by brightness gain over 100 minutes following pressure application suggesting that plants can restore water content in stem after induced embolism. This recovery was limited only to current year wood ring; older wood did not show signs of recovery within the length of experiment (16 hours). In vivo MRI observations of the xylem of moderately stressed (~-0.5 MPa) A. rubrum stems revealed evidence of a spontaneous embolism formation followed by rapid refilling (~30 minutes). Spontaneous (not induced) embolism formation was observed only once, despite over 60 hours of continuous MRI observations made on several plants. Thus this observation provide evidence for presence of naturally occurring embolism-refilling cycle in A. rubrum, but it is impossible to infer any conclusions in relation to its frequency in nature.